1975
DOI: 10.1007/bf00115532
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mechanisms of plasticity enhancement at the superconducting transition

Abstract: The mechanisms of the plasticity enhancement at the N-S transition are considered, based on a comparison of the dependence of this effect on the concentration of defects limiting the dislocation mobility, which, as is shown, is different for competing dynamic models. A method is suggested for determining the role of quasistatic effects, arising due to the inhomogeneity of the dislocation structure of superconductors, in the plasticity enhancement at the N-S transition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1977
1977
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The acceleration of a dislocation moving between two consecutive pinned configurations (over the mean free path, L $ L) was considered in reference. [9] It was shown that, as distinct from the results of reference, [8] for large concentration of pinning points (L < 10 À7 m) the magnitude of Ds NS is to decrease with increasing concentration of the pinning points. A statistical analysis of the role of the inertia effects in thermally activated dislocation motion [10] led to similar conclusions regarding the dependence of Ds NS on the non-dimensional concentration of the pinning points, C ¼ aS À1/2 , where a is the lattice parameter and S is the average area per pinning point.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…The acceleration of a dislocation moving between two consecutive pinned configurations (over the mean free path, L $ L) was considered in reference. [9] It was shown that, as distinct from the results of reference, [8] for large concentration of pinning points (L < 10 À7 m) the magnitude of Ds NS is to decrease with increasing concentration of the pinning points. A statistical analysis of the role of the inertia effects in thermally activated dislocation motion [10] led to similar conclusions regarding the dependence of Ds NS on the non-dimensional concentration of the pinning points, C ¼ aS À1/2 , where a is the lattice parameter and S is the average area per pinning point.…”
Section: Introductionmentioning
confidence: 86%
“…The current models that describe the influence of the transition from the superconducting (S) to the normal (N) state [4][5][6][7] consider the role of the electron drag in the thermally activated overcoming of localized obstacles by moving dislocations, which also involves an effect of the dislocation inertia. [8,9] Under external load, a dislocation, which possesses an effective mass, breaks away from point-like pinning points in a thermally assisted process and moves ahead until it meets a next obstacle. Due to the inertia, the dislocation overshoots the static equilibrium configuration.…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be pointed out that, the inertia was deduced from the mechanical response, rather than being directly observed, and there also existed other interpretations that are not related to inertia, such as the changes in electron drag 15 , 19 , obstacle strength 20 , 21 and mobile dislocation density 22 when entering the superconducting state. Efforts have also been made by Indenbom and Estrin to distinguish between different dynamic models of plasticity enhancement 23 . These experimental results and different theoretical interpretations were summarized and reviewed by Kostorz 24 .…”
Section: Introductionmentioning
confidence: 99%